A relação entre satisfação no trabalho e saúde mental do trabalhador: uma revisão integrativa - Silva, Vanêssa Valério (2008)
Many and increasing are the existing and available scientific studies on workers health, however, these studies provide a range of information that need to be transformed into a knowledge course, organized and synthesized. In this scenario, the challenge is to seek, analyze and synthesize the scientific evidence on the relationship between job satisfaction and Brazilian workers mental health, which can be justified by the importance that this relationship appears to be in the context of health promotion. To achieve this goal, was held an integrative literature review of studies that establish the relationship, published in the Virtual Health Library (VHL) in Portuguese, English and Spanish, from crosses between the descriptors job satisfaction and occupational mental health, workers mental health and job satisfaction, in the years 1997 to 2007. There were 152 (one hundred and fifty-two) studies, while only 26 (twenty-six) met the criteria for inclusion set. Of these, 16 (sixteen) studies are repeated in more than one database and/or in the two searches conducted, and one (1) study was not available after contact with the authors. So were included 8 (eight) studies. From the data found, it appears that there is a statistically significant association between job satisfaction and workers mental health. Clearly the fact that situations of pleasure / job satisfaction, are related to good capacity for work, and the best tables of health, particularly with regard to mental health. In contrast, situations where the work leads to suffering / dissatisfaction, increase to the negative impacts on the mental health of the worker (with emphasis on the Burnout Syndrome, depression and anxiety). It is believed that the quest for workers health promotion must be guided in a "look" at the organizational elements constituents of satisfaction at work, because of its impact on workers mental health. In this sense, it is believed that organizations that seek to promote the health of their workers, should consider the practical knowledge of workers and, through the practice of empowerment, to develop more autonomy and involvement in the process of work and with their own quality of life and health, and, from then you can talk about promoting workers health. Clearly we can see that the search in workers health promotion is still a field of knowledge in construction, where there is shortage of researchers in the field. In addition to research, it is believed that there will only be able to intervene and change the reality in the quest for promoting workers health from the effect of such knowledge in practice achieved in searches. Therefore, it is suggested the holding of longitudinal studies on the subject not found, in multidisciplinary teams, to investigate the causal direction of the associations found. Keywords: Job satisfaction; Workers mental health; Health Promotion; Empowerment.